IMPACT OF EU-ETS ON EUROPEAN AIRCRAFT OPERATORS (Perner's Contacts, 2011)
In 2009 EU Directive 2003/87/EC for inclusion of aviation into the EU Emissions Trading Scheme (EU-ETS) came into force. From January 2012, the EU-ETS will cover virtually all flights departing or arriving in the EU. As aircraft operators will be required to hold emission allowances for all flights that are subject to the EUETS, the economical impact of the system are currently being discussed. This paper aims at describing of current problems of EU-ETS, introducing methods of CO2 monitoring and it describes economical and ecological impact of EU-ETS. This work was supported by the Grant Agency of the Czech Technical University in Prague, grant No. SGS10/221/OHK2/2T/16.
Keywords: EU-ETS; emission allowance; methods of emissions monitoring